Penerapan Algoritma Rought Set Untuk Memprediksi Jumlah Permintaan Produk - Suci Utari (Bulletin of Artificial Intelligence, 2022)
Data Mining is a term used to describe the discovery of knowledge in databases. Data mining is a process that uses statistical, mathematical, artificial intelligence, and machine learning techniques to extract and identify useful information and tied knowledge from large databases. Demand is a number of goods purchased or requested at a certain price and time. Demand is related to consumer desires for goods and services to be fulfilled. And the tendency of consumer demand for goods and services is unlimited. According to the everyday sense of demand is defined in absolute terms, namely the number of goods needed. This way of thinking is based on the idea that humans have needs. For this need, the individual has a demand for goods, the more residents of a country, the greater the public's demand for goods. Rapid Miner is open source software. Rapid Miner is a solution for analyzing data mining, text mining and clustering analysis. Rapid Miner uses a variety of descriptive and predictive techniques to provide users with insights so they can make the best decisions